2013
DOI: 10.4161/rna.24133
|View full text |Cite
|
Sign up to set email alerts
|

On the role of four small hairpins in the HIV-1 RNA genome

Abstract: An RNA secondary structure model for the complete HIV-1 genome has recently been published based on SHAPE technology. Several well-known RNA motifs such as TAR and RRE were confirmed and numerous new structured motifs were described that may play important roles in virus replication. The 9 kb viral RNA genome is densely packed with many RNA hairpin motifs and the collective fold may play an important role in HIV-1 biology. We initially focused on 16 RNA hairpin motifs scattered along the viral genome. We consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 65 publications
4
13
0
Order By: Relevance
“…Strong conservation of these hairpins in some HA subtypes and their disappearance in others is consistent with frequently observed non-random reassortment of compatible segments26303132. In positive-sense mRNA, locally stable structures may be involved in modulation of protein folding, with their folding free energies slowing down the ribosome movement and thus facilitating correct cotranslational formation of native domain structures55, or in interference with host innate immunity5657.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Strong conservation of these hairpins in some HA subtypes and their disappearance in others is consistent with frequently observed non-random reassortment of compatible segments26303132. In positive-sense mRNA, locally stable structures may be involved in modulation of protein folding, with their folding free energies slowing down the ribosome movement and thus facilitating correct cotranslational formation of native domain structures55, or in interference with host innate immunity5657.…”
Section: Discussionsupporting
confidence: 75%
“…Plaque assays of mutant viruses with disrupted or destabilized structures predicted in the HA cleavage site region also did not reveal any replication defects (Supplementary Figs S6 and S7). Similar inconsistency between evolutionary conservation of virus structures and their influence on virus replication assays was previously noted for HIV-1 and murine norovirus5657. It has been suggested that RNA folding could have a function that contributes to virus fitness and persistence in nature but is not essential for basic replication under the experimental conditions.…”
Section: Discussionmentioning
confidence: 56%
“…Computer models of RNA folding predict stable hairpins in these regions that have been suggested to be functional and termed "insulating stems" (10,33). The weak selection against synonymous variants is compatible with the negative results of in vitro replication assays investigating the fitness effects of small RNA hairpins in HIV-1 (43): it would take hundreds of cell culture passages to detect fitness effects of the order of one per thousand. The longitudinal data, however, span many years, and our analysis is able to quantify the subtle fitness effect of RNA structure in intrapatient evolution.…”
Section: Discussionmentioning
confidence: 78%
“…One of the possible functions of structured regions in RNA genomes is to interfere with the host innate systems recognizing a pathogen RNA. 2,[57][58][59] Future experimental studies will elucidate the structurefunction relationships in the influenza virus RNA genome. Apparently, RNA folding is an important factor contributing to the virus evolution.…”
Section: Discussionmentioning
confidence: 99%